2022
DOI: 10.1039/d2dt00816e
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a coordination polymer with sulphate-capped pentamolybdate units and copper: synthesis, structure, magnetic and catalytic studies

Abstract: A new coordination polymer based upon the sulphate-capped pentamolybdate unit has been synthesized from the reaction of {Mo3S7Br6}2- with copper(II) bromide and pyridine, in DMF. The as-synthesized compound, formulated as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 108 publications
0
5
0
Order By: Relevance
“…Mo is another non-noble metal that has been investigated for its ability for various environmental remediation activities such as sulfur removal, hydrogen production, and ammonia degradation [ 102–105 ]. Testing catalysts with MoS 2 as the active phase supported on laponite and laponite modified with Al, Ti, and Zr, Krishnan et al found that the support changed with Zr produced the best results, achieving a conversion of 94% at 600°C ( Figure 7(d–f) ).…”
Section: Ammonia Decomposition Catalystsmentioning
confidence: 99%
“…Mo is another non-noble metal that has been investigated for its ability for various environmental remediation activities such as sulfur removal, hydrogen production, and ammonia degradation [ 102–105 ]. Testing catalysts with MoS 2 as the active phase supported on laponite and laponite modified with Al, Ti, and Zr, Krishnan et al found that the support changed with Zr produced the best results, achieving a conversion of 94% at 600°C ( Figure 7(d–f) ).…”
Section: Ammonia Decomposition Catalystsmentioning
confidence: 99%
“…However, because most polyoxometalates have weak visible-light absorption, only a few polymers derived from polyoxometalates exhibit solar light harvesting ability. 5,6 Pursuing visible-light responsive metal-oxide clusters as monomers for polymer assembly is still on the way. Titanium-oxide clusters (TOCs), 9−14 an important and highly active subgroup of MOCs, are a family of discrete, molecular titanium oxides with sizes comparable to TiO 2 nanoparticles (NPs).…”
Section: Introductionmentioning
confidence: 99%
“…This family of materials has received a lot of interest due to the linear architectures and prospective applications in catalysis, energy storage, and sensing. In general, the properties of the polymeric material are determined by the nature of the monomers and the coordinate mode between the monomers. Recently, several functionalized metal-oxide clusters (MOCs), notably polyoxometalates, , have been widely employed in the fabrication of a wide range of polymeric materials with feature dimensions of approximately one nanometer. , Given the current research interests in sustainable chemistry and functional polymeric materials, it would be intriguing to employ visible-light-responsive monomers to develop one-dimensional coordination polymers with desirable photo-responsive properties. However, because most polyoxometalates have weak visible-light absorption, only a few polymers derived from polyoxometalates exhibit solar light harvesting ability. , Pursuing visible-light responsive metal-oxide clusters as monomers for polymer assembly is still on the way.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Derivatives of 1,3,4-thiadiazoles are widely used in coordination chemistry as ligands [42][43][44], in the synthesis of polymers [45], and the creation of polymer films [46,47]. The prospects of using 1,3,4-thiadiazoles in optoelectronics [48], in the purification of water from heavy metal ions [49], for the separation of minerals by the flotation method [50], and the creation of corrosion-resistant coatings [51] are discussed in the literature.…”
Section: Introductionmentioning
confidence: 99%